The impact of knowledge of HPV positivity on cytology triage in primary high-risk HPV screening. (December 2019) - Aitken, Clare A; Holtzer-Goor, Kim M; Uyterlinde, Anne; van den Brule, Adriaan JC; van der Linden, Hans C; Huijsmans, Cornelis J; de Kok, Inge MCM; van Kemenade, Folkert J
Objective: Several studies have shown that there is an upward shift in the classification of cervical cytology when high-risk human papillomavirus (hrHPV) status is known to be positive. The Netherlands implemented primary hrHPV screening with reflex cytology as the primary screening test in 2017. Prior to implementation of the new programme, we investigated whether knowledge of hrHPV status influences cytology rating. Methods: Using a set of 200 cytology slides that had been previously tested, two pairs of cytotechnicians rated 100 slides per pair twice: first without knowledge of hrHPV status and then, after a wash-out period of two months, with knowledge of hrHPV status. Results: We found that hrHPV positive slides were more likely to be rated up over the referral threshold (i.e. from negative for intraepithelial lesion or malignancy to atypical squamous cells of undetermined significance+) than hrHPV negative slides at the second review when hrHPV status was known (relative risk = 3.2; 95% confidence interval: 1.3–7.9). Conclusions: If the same upward shift in ratings were to be observed in the national programme, it may have implications for referrals of women with low-grade lesions.